Analysis of The Impact of Funding, Lending, and Digital Banking on The Financial Perfomance of The Banking Sektor - Rahmadhany, Khoirin Nissa; Wahyudi, Henri Dwi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
The purpose of this research is to analyze the impact funding, lending, and digital banking on the financial performance of the banking sector during the 2021-2023 periods. This type of research is descriptive quantitative, using secondary data from banks financial report of the 15 commercial banks listed on the Indonesia Stock Exchange (IDX). Data analysis was conducted using panel data multiple linear regression with a fixed effect model in E-Views 12. The results show that funding has a positive and significant impact on financial performance. Lending also has a positive impact, although it doesn’t significantly on the financial performance. Digital banking has no positive effect on financial performance. However, it has significant impact. While simultaneously the three variables have a positive and significant effect on financial performance. The results of this research indicate the importance of digital banking development and effective management of funding and lending to improve financial performance. Therefore, banks need to formulate strategies that include digital banking services and improve efficiency in fund management and credit distribution.